2018
DOI: 10.1097/adm.0000000000000380
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use Disorders Attributed to Tramadol Among Egyptian University Students

Abstract: Tramadol use was common among university students, with higher prevalence among males. There is a considerable relationship between tramadol use, smoking, and use of other substances. Further population-based longitudinal studies need to investigate the causal relationship between tramadol use, smoking, and use of other substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 31 publications
4
41
1
Order By: Relevance
“…Although tramadol remains largely unregulated in the developing world, the rates of misuse and awareness of the risks have been increasing outside the US. 38 39 40 41 Data to support the avoidance of long acting opioids in the acute setting remain strong, 42 43 44 but no clear data are available on the risks versus benefits of other short acting opioids compared with tramadol. Therefore, the choice to prescribe tramadol rather than another short acting opioid remains largely dependent on the provider and scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Although tramadol remains largely unregulated in the developing world, the rates of misuse and awareness of the risks have been increasing outside the US. 38 39 40 41 Data to support the avoidance of long acting opioids in the acute setting remain strong, 42 43 44 but no clear data are available on the risks versus benefits of other short acting opioids compared with tramadol. Therefore, the choice to prescribe tramadol rather than another short acting opioid remains largely dependent on the provider and scenario.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, tramadol misuse has increased significantly in the Middle Eastern and African regions, turning this issue into a notable public health problem [108]. Studies from Egypt showed a high rate of 8.8 to 12.3% of tramadol use among high school and university students [106,109]. Self‐reported prevalence of knowing someone who currently uses tramadol was 2.4% in the Iraqi general population [110].…”
Section: Discussionmentioning
confidence: 99%
“…The abuse potential of tramadol has become a particular concern in Egypt and other African countries (40), which have also observed increases in the importation of illicit and adulterated tramadol (41). Tramadol abuse among adolescents and young adults in those countries has been reported to be as high as 8.8% - 12.3%, respectively (42, 43). These countries petitioned the WHO to consider placing tramadol under international control (41) and the WHO Expert Committee on Drug Dependence responded in 2018 by conducting a critical review of tramadol.…”
Section: Introductionmentioning
confidence: 99%